Thrust allocation algorithm considering hydrodynamic interactions and actuator physical limitations. - Arditti, Felipe (2019)
The Dynamic Positioning (DP) System is responsible for the station keeping of vessels in several offshore operations. The forces required by the DP System are distributed among the available thrusters by a thrust allocation algorithm which should be accurate, efficient and robust. This means that the effective forces match the required forces while power consumption is minimized. Additionally, in case of impossibility of generating the required forces the heading of the vessel is maintained to avoid increasing environmental forces. To accurately generate the required forces, the physical limitations of the thrusters and the hydrodynamic interactions must be considered. The hydrodynamic interactions are consistently modelled to accommodate the following typical effects: thruster-hull, thruster-current and thruster-thruster interaction. The result of this modeling is a nonlinear optimization problem, which is solved using the Sequential Quadratic Programming (SQP) algorithm with slack variables. The DP simulation carried out show that by considering the hydrodynamic interactions on thrust allocation the overall performance (controllability and power consumption) of the DP system is improved.